VS SYNTACTIC CONFIGURATIONS IN ROMANCE ADVERBIAL CLAUSES : Received: 28th February 2022; Revised: 27th March 2022, 1st April 2022; Accepted: 10th April 2022 - Bodoc, Alice Magdalena (PEOPLE: International Journal of Social Sciences, 2022)
Based on an original corpus, and also on the important contributions of Haegeman 2012, Pană Dindelegan & Maiden 2013, and Lahousse 2010, I intend to demonstrate in this article that there are specific factors that influence the VS syntactic configurations of Romance languages (Romanian, Italian, and French), and these factors are directly connected to the internal information structure. From a methodological point of view, this is an empirical study, combining comparative and corpus analyses, qualitative and quantitative observations, and using the instruments of Morphosyntax and Pragmatics. In the end, the results of the analysis highlight the idea that both information structure and the “pro-drop” feature have a big impact on the word order of the constituents, generating a significant discrepancy between Romanian and Italian, on the one hand, and French, on the other hand.